The Effect of Thinking Like a Nurse Simulation as an Online Clinical Learning Method on Nursing Students’ Satisfaction and Confidence during the COVID-19 Pandemic - Dian Fitria; Jehan Puspasari; Puspita Hanggit Lestari (Universitas Airlangga, 2021)
Introduction: Corona Virus Disease (Covid-19) was declared as a pandemic by the World Health Organization (WHO) resulting in changes in existing patterns of life. This impact also affects the world of education, including nursing vocational education. Nursing vocational education must be able to design online methods for the clinical competency with existing facilities and infrastructure. The online clinical method can describe the achievements achievable in clinical facilities so as to build students’ satisfaction and confidence.Methods: This research used quasi-experimental pre-posttest without control group method by providing clinical learning thinking like a nurse simulation. The research sample consists of 110 diploma students with purposive sampling method. Simulation focuses on clinical judgment, communication skills, and skill simulations by adopting clinical practice in hospitals. Assessment is measured using Simulation Design Scale (SDS) and Student Satisfaction and Self-Confidence in Learning Scale (SCLS). Pair t test with level of significance 0.05 is used to process data.Results: It is found that there is an increase in students’ satisfaction and confidence using the clinical simulation method of “thinking like a nurse” having an average 40.69%. Meanwhile, online clinical learning methods has an average increase of 114%. There is an effect of thinking like a nurse simulation method on students’ satisfaction and self-confidence (p < 0.05).Conclusion: This research is recommended to add to the reference for online nursing clinical learning methods during Covid-19. Determining the ratio between students and lecturers in online clinic learning can be considered for further research.